Kinetics of (14)C-Photosynthate Uptake by Developing Soybean Fruit - Thorne, John H. (1980)
By pulse-labeling field-grown soybean leaves for 60 seconds at midday with (14)CO(2) and then sequentially harvesting, dissecting, and extracting the radioactive fruit tissues (of pod and seeds), the route, uptake kinetics, and metabolic fate of (14)C-photosynthate as it was imported by 35- to 40-day-old pods were determined. As the [(14)C]sucrose pulse entered the pods, the seeds became radioactive immediately but a lag of nearly 30 minutes occurred before label could be detected in the pod wall pericarp. Import of the (14)C-pulse by the seeds was exclusively via the seed coats, where rapid unloading occurred. Maximum accumulation of label in the seed coat occurred in about 60 minutes at which time 59% of the total radioactivity in the fruit was in the three seed coats, whereas only 7% was in the cotyledons they enclosed. The photosynthate remained as [(14)C]sucrose as it passed through the seed coat, but appeared to be hydrolyzed relatively soon after uptake by the cotyledons. By 2.5 hours, 60% of the (14)C-photosynthate pulse had passed into the cotyledons with only 27% remaining in the seed coats. Inasmuch as there is no vascular connection between maternal seed coat and the developing embryo, cotyledonary uptake of sucrose released from the inner seed coat surface may require specialized transport mechanisms.